2013
DOI: 10.3109/09546634.2013.777151
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of non-ablative fractional laser photothermolysis: a retrospective study of 856 treatments in 362 patients

Abstract: Non-ablative fractional laser skin treatment has a relatively low complication rate. The adverse events found were temporary and did not result in long-term or severe sequelae such as hypertrophic scarring, atrophic scarring or permanent pigmentary alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…Procedure pain was reported as mild to moderate in most subjects and adverse events were generally limited to immediate post‐treatment trace‐to‐moderate erythema and edema. No long‐term or serious adverse events reported, as seen in previous studies . Downtime following individual treatments lasted less than 2 days in most cases.…”
Section: Discussionsupporting
confidence: 68%
“…Procedure pain was reported as mild to moderate in most subjects and adverse events were generally limited to immediate post‐treatment trace‐to‐moderate erythema and edema. No long‐term or serious adverse events reported, as seen in previous studies . Downtime following individual treatments lasted less than 2 days in most cases.…”
Section: Discussionsupporting
confidence: 68%
“…The first clinical study using an early 1,550‐nm erbium fiber prototype demonstrated mild‐to‐moderate improvement in periorbital wrinkles and skin texture in Caucasian patients after four treatments . Efficacy in improving wrinkles, skin texture, pore size, and dyspigmentation in the Asian population has similarly been demonstrated . Given the increased risk of PIH, a greater number of treatments with lower density is the preferred approach in treating skin of color.…”
Section: Non‐ablative Fractional Therapymentioning
confidence: 99%
“…In a retrospective review of 362 patients undergoing a total of 856 NAFL treatments with either 1,550‐nm erbium or 1,927‐nm thulium fiber laser, significant adverse events occurred in only 5%. This included prolonged erythema (>7 days) in 1.8%, PIH in 1.1%, and worsening of melasma in 0.9% .…”
Section: Non‐ablative Fractional Therapymentioning
confidence: 99%
“…[1][2][3] Many studies have proven that this treatment modality can achieve desirable clinical results without serious adverse effects or longer downtime, which was the major limitation of ablative laser resurfacing. [4][5][6] Nonablative fractional laser therapy at 1,550 nm was approved by FDA for the treatment of periorbital rhytides, skin resurfacing, acne, and surgical scars. 5 It was also approved as an effective treatment modality for melasma and pigmented lesions.…”
Section: Introductionmentioning
confidence: 99%
“…When we consider the treatment of photoaging in Asian skin, dyspigmentation and postinflammatory hyperpigmentation always matters. 4 The modality to treat skin pigmentation, texture and wrinkles at the same time, is a must to ensure patient higher satisfaction. Therefore, dermal remodeling with 1,550 nm fractional laser treatment as well as improvement of superficial pigmentation and skin tones targeted by 1,927 nm thulium fiber fractional laser in a single session can be a promising treatment modality especially for photorejuvenation in Asian patients.…”
Section: Introductionmentioning
confidence: 99%